2014
DOI: 10.1007/s11552-014-9670-6
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Comparison of Local Anesthesia with or without Sedation for Minor Hand Surgery

Abstract: Background The purpose of this study was to assess satisfaction and pain intensity in patients undergoing minor hand surgery under local anesthesia (LA) with or without sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Although it is clear that surgeons have several options to consider when performing trigger finger release (TFR) surgery for appropriately indicated patients, including choice of surgical setting and anesthetic type, the associated cost implications are less clear but may be substantial. With regard to anesthetic type, performing TFR under local anesthetic without sedation has been shown to be effective, 710 while other anesthetic methods including Bier block, monitored anesthesia care (MAC), regional block, or general anesthesia are also well-established options.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is clear that surgeons have several options to consider when performing trigger finger release (TFR) surgery for appropriately indicated patients, including choice of surgical setting and anesthetic type, the associated cost implications are less clear but may be substantial. With regard to anesthetic type, performing TFR under local anesthetic without sedation has been shown to be effective, 710 while other anesthetic methods including Bier block, monitored anesthesia care (MAC), regional block, or general anesthesia are also well-established options.…”
Section: Introductionmentioning
confidence: 99%
“…Only 4.9 % of patients had surgery under local anesthesia alone. Local anesthesia was associated with more events in the surgery center and more post-discharge problems, perhaps related to pain [21]. The fact that involvement of an anesthesiologist and/or CRNA was associated with more perioperative and postoperative events might be related to problems associated with IV sedation, but may also reflect co-existing medical conditions in this population that led to the need for oversight by a skilled anesthesia provider.…”
Section: Discussionmentioning
confidence: 96%
“…We found that local anesthesia, IV sedation and regional anesthesia were rather associated with perioperative symptoms in the ambulatory surgery center than general anesthesia. This can be explained with more pain [21]. In addition, this is however speculative, patients after general anesthesia are better informed about the early postoperative course.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a tourniquet was used on all patients. 12 This study has some weaknesses. First, there may be some selection bias as the patients were not randomized.…”
Section: Discussionmentioning
confidence: 96%